Szpiegostwo w znowelizowanym Kodeksie karnym - Hoc, Stanisław (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This article discusses the amendment to Article 130 of the Penal Code, which introduced new forms of the crime of espionage while tightening criminal liability. Some of the new legal solutions are controversial.
Keywords: espionage; foreign intelligence; disinformation; news